Improving the Lives of Patients with Alpha-1 Antitrypsin Deficiency - Sandhaus, Robert A (Int J Chron Obstruct Pulmon Dis, 2020)
Alpha-1 Antitrypsin Deficiency (AATD) is a rare genetic condition that predisposes patients to lung and liver disease and is often underdiagnosed due to incomplete diagnosis of chronic obstructive pulmonary disease (COPD) and asthma. Improvements in physician awareness have been made, but better strategies for both diagnosis and management are still required. The only current disease-modifying therapy for AATD is the infusion of the missing Alpha-1 Antitrypsin (AAT) protein, which can slow progression of emphysema. However, AAT treatment can impact patient freedom and quality of life due to the need for weekly intravenous infusions. A symposium was held to discuss patient-centric aspects of care that have impact on the lives of patients with AATD, including exacerbations of their lung disease, self-administration of intravenous AAT therapy and pulmonary rehabilitation. Intravenous self-infusion of drugs is an established treatment strategy for patients with a variety of conditions and can improve patient quality of life, freedom and mental well-being. Experience from these areas show that patients typically manage their treatment well and without complications. When applied to AATD, training patients to self-infuse therapy can be successful, but formal guidelines would be beneficial. In addition to pharmacological intervention, individualized pulmonary rehabilitation, exercise and educational programs can encourage health-enhancing patient behavior and further improve patient quality of life. However, differences in skeletal muscle adaptations to pulmonary rehabilitation exercise regimens have been observed between patients with AATD and non-AATD COPD, highlighting the need to develop training programs specifically designed for patients with AATD.